Analisis Teknik Permainan Gitar Klasik Karya Frederich Chopin: Nocturne In E-Flat Major Op.9 No.2 - Muhammad Ibrahim; Tulus Handra Kadir (SENDRATASIK UNP, 2022)
This study aims to determine how the song nocturne in e-flat major op 9 no 2 by Fredrich Chopin is technically expressed through the classical guitar playing by Francisco Tarrega. This research is descriptive analysis, which in this case describes, outlines and describes the technique of playing nocturne in e-flat major op 9 no 2 which is played for classical guitar instruments. The object of this research is the classical guitar playing technique in nocturne in e-flat major op 9 no 2 by Frederich Chopin. The research instrument is the researcher himself is assisted by several equipment to process the data. The type of data used is primary data and secondary data. The steps to analyze the data were done by using interview, observation and documentation techniques. The data are organized and interpreted as finding material to answer research problems. The results showed that the techniques used in the classical guitar song nocturne in e-flat major op 9 no 2, namely arpeggio, legato, slur, glissando, barre, harmonic, appoggiatura, and trill. Tarrega replaced techniques that can also be played on guitar such as upper mordent, group peto, and staccato with slur techniques, and glissando, then condensed the rhythmic tone with a 1/32 note. The substitution of this technique is due to organological reasons, where the piano has a soft pedal and a damper pedal that can maintain the tone, while this is not possible on a guitar. The difference in the use of playing techniques or more precisely the adjustment of the playing technique of this work using classical guitar gives different nuances to its expression, namely sharp, deep, sad, mellow, firm, fast, free, bright, broad nuances on the piano. While the guitar creates a soft, gentle, broad, crowded, fast feel.